Characterisation and evaluation of physical properties of AH-Plus sealer with and without the incorporation of petasin, pachymic acid, curcumin and shilajit-an invitro study - Selvanathan MJ Vinola; Sekar Mahalaxmi (BMC, 2024)
Abstract Background AH Plus, an epoxy resin-based sealer, is widely used in endodontic practice, owing to its good physical properties that confers longstanding dimensional stability and good adhesion to dentin. Nevertheless, its propensity to trigger inflammation, especially in its freshly mixed state, has been extensively documented. Phytochemicals such as Petasin, Pachymic acid, Curcumin, and Shilajit are known for their anti-inflammatory and analgesic effects. This study aimed to analyze and determine the effect of these natural products on the physical properties of AH Plus sealer when incorporated with the sealer. Methods AH Plus (AHR) sealer was mixed with 10% petasin, 0.75% pachymic, 0.5% and 6%shilajit to obtain AHP, AHA, AHC and AHS in the ratio of 10:1 and 5:1 respectively. Five samples of each material were assessed for setting time, solubility, flow, and dimensional stability in accordance with the ISO 6876:2012 standardization. Sealers were characterized through scanning electron microscopy (SEM), X-ray energy dispersive spectroscopy, X-ray diffraction (XRD), and Fourier transform infrared (FTIR) spectroscopy. Statistical evaluation involved the Kolmogorov-Smirnov and Shapiro-Wilks tests for normality and the one-way ANOVA test for analysis. Results In this investigation, the characterisation analysis revealed a relatively similar microstructure in all the experimental root canal sealers. All experimental groups, excluding the control group, exhibited an increase in flow ranging from 11.9 to 31.4% at a 10:1 ratio. Similarly, for the 5:1 ratio, the increase ranged from 12.02 to 31.83%. In terms of dimensional stability, all groups at the 10:1 ratio showed a decrease compared to the control group. The addition of natural agents to AHR in 10:1 ratio led to a reduction in setting time by 8.9-31.6%, and at a 5:1 ratio, the reduction ranged from 8.1 to 31.5%. However, regarding solubility, the addition of natural agents did not induce any significant alterations. Conclusion Based on the results of this study, it can be concluded that all tested root canal sealers exhibited properties that met the acceptable criteria outlined in the ISO 6876:2012 standardization.